Evaluation of the Hematologic Safety of Same Day Versus Standard Administration (24- to 72-Hour Delay) of Pegfilgrastim in Gynecology Oncology Patients Undergoing Cytotoxic Chemotherapy. Issue 7 (September 2015) - Billingsley, Caroline C.; Jacobson, Samuel N.; Crafton, Sarah M.; Crim, Aleia K.; Li, Quan; Hade, Erinn M.; Cohn, David E.; Fowler, Jeffrey M.; Copeland, Larry J.; Salani, Ritu; Backes, Floor J.; O'Malley, David M.
<x xml:space="preserve">Abstract</x> Objective We assessed the safety and efficacy of administration of pegfilgrastim on the same day compared with standard administration 24 to 72 hours after chemotherapy in patients with gynecologic malignancies. Methods A retrospective review was conducted on patients undergoing pegfilgrastim to mitigate the myelosuppressive consequences of chemotherapy. The primary outcome was incidence of grade 3 to 4 neutropenia following pegfilgrastim for same-day administration (D1) versus standard administration (D2+). Secondary outcomes included dose delay, regimen change, hospitalization due to neutropenia, and incidence of febrile neutropenia. Results Four hundred twenty-one patients with 2071 administrations of pegfilgrastim were included. Five hundred six administrations of pegfilgrastim were given on D1 compared with 1565 administrations on D2+. The most common malignancy was ovarian cancer (79.1%), followed by endometrial (14.5%). Comparing the D1 and D2+ cohorts, noninferiority was not established for the incidence of grade 3 to 4 neutropenia (2.6% vs 1.8%, adjusted relative risk [aRR], 1.6; 90% confidence interval [CI], 0.87–3.2) or dose modification (6.5% vs 4.9%; aRR, 1.3; 90% CI, 0.9–1.8). However, the rate of treatment delays (7.3% vs 9.4%; aRR, 0.8; 90% CI, 0.6–1.1) in the D1 and D2+ groups suggested that delays in the D1 group were not more common than in the D2+ group. Conclusions The incidence of hematologic toxicities and dose modification in patients receiving same-day pegfilgrastim were not as low as in those undergoing standard administration. However, treatment delays were found to be no more frequent in those receiving same-day pegfilgrastim versus standard administration. Same-day administration of pegfilgrastim is a reasonable option.